Using BIB-SEM Imaging for Permeability Prediction in Heterogeneous Shales. (23rd October 2017) - Sinn, C. J. A.; Klaver, J.; Fink, R.; Jiang, M.; Schmatz, J.; Littke, R.; Urai, J. L.
Abstract : Organic-rich shale samples from a lacustrine sedimentary sequence of the Newark Basin (New Jersey, USA) are investigated by combining Broad Ion Beam polishing with Scanning Electron Microscopy (BIB-SEM). We model permeability from this 2D data and compare our results with measured petrophysical properties. Three samples with total organic carbon (TOC) contents ranging from 0.7% to 2.9% and permeabilities ranging from 4 to 160 nD are selected. Pore space is imaged at high resolution (at 20, 000x magnification) and segmented from representative BIB-SEM maps. Modeled permeabilities, derived using the capillary tube model (CTM) on segmented pores, range from 2.3 nD to 310 nD and are relatively close to measured intrinsic permeabilities. SEM-visible porosities range from 0.1% to 1.8% increasing with TOC, in agreement with our measurements. The CTM predicts permeability correctly within one order of magnitude. The results of this work demonstrate the potential of 2D BIB-SEM for calculating transport properties of heterogeneous shales.